Revealing the Impact of Waqf Literacy: How are Students of Universitas Darussalam Gontor Interested in Cash Waqf? - Zahro', Khurun’in; Anisa Muflikhatul Muna; Vina Fithriana Wibisono (ZISWAF ASFA, 2025)
This study aims to identify the effect of cash waqf literacy on interest in waqf money among female teachers of Universitas Darussalam Gontor at Pondok Modern Darussalam Gontor for Girls 3. Innovation in waqf management is a necessity to expand Muslim participation, especially in the form of cash waqf. The cash waqf model provides greater flexibility, given that the object can be both movable and symbolic, allowing for more diverse investments and utilization. However, the potential of cash waqf in Indonesia has not been fully maximized. This research is descriptive quantitative research, data collection techniques using questionnaires, with proportional random sample sampling of 160 respondents. The analytical tool used is SEM-PLS Version 4.0. The results showed that the level of cash waqf literacy in female students at Universitas Darussalam Gontor  was at a moderate level, namely at a percentage of 65.63%. Factor analysis shows that cash waqf literacy has a significant influence on the interest in waqf money among these students. Evidenced by the t-statistic value of 37,188 (p-value 0.000 <0.05). In a 95% interval, the effect of waqf literacy on interest in waqf money lies between (0.776) to (0.867). The research shows that waqf literacy can influence the interest in waqf money among female students at Universitas Darussalam Gontor, especially Pondok Modern Darussalam Gontor for Girls 3.